Overview of the toxic effects of titanium dioxide nanoparticles in blood, liver, muscles, and brain of a Neotropical detritivorous fish - Carmo, Talita L. L. [UNESP]; Siqueira, Priscila R.; Azevedo, Vinicius C. [UNESP]; Tavares, Driele [UNESP]; Pesenti, Emanuele C.; Cestari, Marta M.; Martinez, Claudia B. R.; Fernandes, Marisa N. (Wiley-Blackwell, 2019)
The toxicity of titanium dioxide nanoparticles (TiO2-NP) in the blood, liver, muscle, and brain of a Neotropical detritivorous fish, Prochilodus lineatus, was tested. Juvenile fish were exposed to 0, 1, 5, 10, and 50 mg L-1 of TiO2-NP for 48 hours (acute exposure) or 14 days (subchronic exposure) to evaluate changes in hematology, red blood cell (RBC) genotoxicity/mutagenicity, liver function (reactive oxygen species (ROS) production, antioxidant responses, detoxification, and histopathology), acetylcholinesterase (AChE) activity in muscles and brain, and Ti bioaccumulation. TiO2-NP did not cause genetic damage to RBC, but acutely decreased white blood cells (WBC) and increased monocytes. Subchronically, RBC decreased, mean cell volume and hemoglobin increased, and WBC and lymphocytes decreased. Therefore, NP has the potential to affect immune system and increase energy expenditure, reducing the fish's ability to avoid predator and to resist pathogens. In the liver, acute exposure decreased ROS and increased glutathione (GSH) content, while subchronic exposure decreased superoxide dismutase activity and increased glutathione-S-transferase (GST) activity and GSH content. GSH and GST seem to play an essential role in metabolizing NP and ROS, likely increasing hepatocytes' metabolic rate, which may be the cause of observed cell hypertrophy, disarrangement of hepatic cords and degenerative morphological alterations. Although most studies indicate that the kidney is responsible for metabolizing and/or eliminating TiO2-NP, this study shows that the liver also has a main role in these processes. Nevertheless, Ti still accumulated in the liver, muscle, and brain and decreased muscular AChE activity after acute exposure, showing neurotoxic potential. More studies are needed to better understand the biochemical pathways TiO2-NP are metabolized and how its bioaccumulation may affect fish homeostasis and survival in the environment.
Keywords: bioaccumulation; glutathione-S-transferase neurotoxicity; immune system; reactive oxygen species